Fabrication of MEMS mold with inclined micro-multi-fin structure and shape transfer to resin by thermal imprint process. (6th March 2020) - Yahagi, T.; Murayama, H.; Watanabe, Y.; Mineta, T.
Abstract: In this paper, we describe the fabrication of horizontal and inclined micro-multi-fin structures and discuss the experimental results of the shape transfer to resin material. Using the MEMS fabrication process, micro-mold structures with microscale ridge structures and several-hundred-nanometer-sized multi-fin structures at the scale of a morpho butterfly were fabricated on Si substrates. The shape transfer to the resin material was examined using a thermal imprinting process. In both mold types, the resin was injected into the narrow gaps of the multi-fin structures of the mold. It was difficult to release the resin in the horizontal multi-fin from the mold. Conversely, with the inclined-type, the multi-fin shape was successfully transferred to the resin and released without fracture (2  μ m pitch ridge structure with a 0.2  μ m pitch inclined multi-fin structure). The optical reflection of the inclined molded COP resin was evaluated, exhibiting a light blue reflection.